Effects of the Multidimensional Treatment on Pain, Disability, and Sitting Posture in Patients with Low Back Pain: A Randomized Controlled Trial - Tae-Sung In; Jin-Hwa Jung; Kyoung-Sim Jung; Hwi-Young Cho (Pain Research and Management)
The purpose of this study was to investigate the effects of multidimensional approach model on the pain, disability, and sitting posture in patients with nonspecific low back pain (LBP). Sixty LBP patients were recruited and were randomly divided into two groups: multidimensional treatment (MT) group (n = 30) and unimodal treatment (UT) group (n = 30). All participants underwent 48 sessions of treatment (40 min/session, two sessions per day, 2 days per week) for 12 weeks. The MT group conducted a core stability exercise twice a day and additionally provided training on pain principles and management methods. The UT group only performed a core stability exercise twice a day. The visual analog scale (VAS) and Oswestry Disability index (ODI) were used to measure pain intensity and disability. Thoracolumbar kyphosis and lumbar lordosis in the sitting position were measured using a motion capture system. After training, the pain and disability in the MT group improved significantly greater than the UT group (p<0.05). In the MT group, the pain relief effect persisted 3 months after the end of training. Thoracolumbar kyphosis and lumbar lordosis in the MT group were significantly improved compared to the UT group (p<0.05). Thus, MT combined with core stability exercise may be used to improve the pain, disability, and sitting posture in patients with LBP.